Satu Rasa Dalam Keindahan Nusantara Pertukaran Mahasiswa Merdeka Angkatan Dua - Elza L.L. Saragih; Delavia Sihombing (Jurnal Mahasiswa Kreatif, 2023)
The Merdeka Learning Campus Merdeka Program (MBKM which has been running at the Faculty of Language and Literature education and all faculties of education at the University of HKBP Nommensen Medan) is considered to have an impact on the quality of learning and student quality. This study analyzes the impact of MBKM on student quality from the perspective of FKIP students. Based on the results of a survey analysis of 224 respondents, FKIP students who interact directly with inbound students, found a positive impact on student quality. The biggest impact is seen in increasing diversity tolerance and accepting differences. Apart from that, FKIP Nommensen Medan students also felt an increase in their communication and collaboration skills.